(untitled) (قضايا سياسية, 2025)
climate change is considered one of the strategic challenges threatening the global strategic environment and international stability. it results in both internal and international conflict as well as recurring health crises , due to shifts in climate balance that are beyond human control , in addition to human -induced activities this challenge is strategically exploited by influential powers with in the global strategic environment to serve their higher national interest . attention to this challenge is often directed toward undermining adversaries either by seeking to limit their economic growth, exporting new technologies adapted to climate change to less technologically advanced nation , or portraying these influential powers as normative actors committed to preserving human life despite their own contribution to the onset of climate cgange.